2020
DOI: 10.1080/17476348.2020.1761791
|View full text |Cite
|
Sign up to set email alerts
|

The role of essential organ-based comorbidities in the prognosis of COVID-19 infection patients

Abstract: Objectives: To assess the role of essential organ-based comorbidities in the prognosis of COVID-19 patients. Methods: All consecutive patients diagnosed with COVID-19 admitted to the Zhongnan Hospital of Wuhan University from 11 January to 16 March 2020 were enrolled in this retrospective cohort study.Results: A total of 212 COVID-19 patients were included. COVID-19 patients with heart, liver and kidneycomorbidity, compared to patients without related comorbidities, were more likely to have cardiac injuries [9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 11 publications
(17 reference statements)
3
30
0
2
Order By: Relevance
“…Cheng et al 19 emphasize that patients with a history of CKD exhibit a pro-inflammatory state with functional defects in innate and acquired immunity and are recognized as a population at greater risk for infections. However, this alone is not enough to explain the frequent occurrence of AKI in COVID-19 patients, and perhaps it only corroborates what was demonstrated by Yang et al 32 , who demonstrated that patients with kidney comorbidities are more susceptible to the development of AKI, although this does not apply exclusively to them. Pei et al 29 suggested that the severity of pneumonia was the main risk factor for the development of AKI in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Cheng et al 19 emphasize that patients with a history of CKD exhibit a pro-inflammatory state with functional defects in innate and acquired immunity and are recognized as a population at greater risk for infections. However, this alone is not enough to explain the frequent occurrence of AKI in COVID-19 patients, and perhaps it only corroborates what was demonstrated by Yang et al 32 , who demonstrated that patients with kidney comorbidities are more susceptible to the development of AKI, although this does not apply exclusively to them. Pei et al 29 suggested that the severity of pneumonia was the main risk factor for the development of AKI in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 63%
“…The pathogenesis of kidney injury in COVID- 19 has not yet been defined, but it has been observed that the presence of comorbidities can influence its development 32 . In this sense, Yang et al 32 have shown an incidence of kidney injury in patients with renal comorbidities significantly higher than in those without comorbidities (54.5% vs 2.0%, p<0.001). Cheng et al 19 found that out of all the patients with abnormalities in kidney function, 13% had an underlying kidney disease and 2% a history of chronic kidney disease (CKD).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The direct impact of SARS-CoV-2 infection and the COVID-19 pandemic on morbidity, mortality and healthcare resource use across the globe has rightly been the focus of much research. NCDs have also featured prominently given the interaction between underlying health conditions and the likelihood of adverse outcomes during the infection [11][12][13]. Perhaps less frequently, but no less importantly, some have drawn attention to the detrimental impact that the focus on COVID-19 will have on the medium to long term management and outcomes for many common NCDs [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…respiratory rate and arterial pressure); 11,12 laboratory abnormalities including inflammatory, coagulation and organ-specific studies (e.g. lactate dehydrogenase, D-dimer, fibrinogen, cardiac troponins, liver function tests, among others), 5,6,[8][9][10]13 and lung imaging findings (e.g. number of affected lobes and estimated pneumonia extension).…”
Section: Introductionmentioning
confidence: 99%